Research Advances and Prospects of Orphan Genes in Plants - Jiang, Mingliang; Li, Xiaonan; Dong, Xiangshu; Zu, Ye; Zhan, Zongxiang; Piao, Zhongyun; Lang, Hong (Frontiers in Plant Science, 2022)
Orphan genes (OGs) are defined as genes having no sequence similarity with genes present in other lineages. OGs have been regarded to play a key role in the development of lineage-specific adaptations and can also serve as a constant source of evolutionary novelty. These genes have often been found related to various stress responses, species-specific traits, special expression regulation, and also participate in primary substance metabolism. The advancement in sequencing tools and genome analysis methods has made the identification and characterization of OGs comparatively easier. In the study of OG functions in plants, significant progress has been made. We review recent advances in the fast evolving characteristics, expression modulation, and functional analysis of OGs with a focus on their role in plant biology. We also emphasize current challenges, adoptable strategies and discuss possible future directions of functional study of OGs.